Urban intervention of the village of Pachabamba: Context analysis and proposal of articulated spaces - Daga Almerco , Bekin Bauer (2025)
In the town of Pachabamba, urban planning faces the challenge of integrating sustainable land use with the orderly development of the area. Using a quantitative approach, the analysis of the current characteristics of the environment identified both strengths and weaknesses that can be taken into account to propose viable strategies to optimize land use. These strategies include the integration of agricultural and residential areas, articulated public spaces and recreational areas, with the aim of creating a functional, balanced and sustainable environment. The intervention also contemplates the improvement of the existing infrastructure and the implementation of new communication routes, conceived to facilitate mobility, stimulate the economy and strengthen the social development of the town. The proposals seek to respond to the real needs of residents, promoting a positive long-term impact. In conclusion, it is highlighted that adequate urban planning, based on a quantitative approach and sensitive to local particularities, can transform Pachabamba into a model of sustainable rural development. This would not only benefit its inhabitants in terms of quality of life, but would also consolidate the town as an attractive tourist destination and a strategic axis for regional development.